Processo de escolarização em Antônio Prado - RS (1886-1920) : culturas e sujeitos - Bernardi, Manuela Ciconetto (My University, 2020)
The present dissertation narrates the schooling process in Antônio Prado - RS between 1886 and 1920. The study is linked to the History and Philosophy of Education Research Line Of the Graduate Program in Education at the University of Caxias do Sul. The initial time frame, 1886, refers to the creation of the colony and the establishment of the first immigrants, while 1920 corresponds to the beginning of the school activities of the Marist Brothers, as it is another stage in the school process of the municipality. The theoretical and methodological assumptions that guide the research come from Cultural History and the History of Education, from the contributions of Certeau (1982, 1995), Febvre (1989), Le Goff (1990a, 1990b), Burke (1992, 2004, 2008), Chartier (1991a, 1991b, 2002a, 2002b, 2009, 2019) and Hall (2006) for the understanding of historical-documentary research, of subjects and representations. While the understanding of school cultures, practices and modes of schooling it is based on Viñao Frago (1993, 1995, 2000 and 2005), Viñao Frago and Escolano (1998), Julia (2001), Faria Filho (2002, 2008), in addition to researchers who dialogue with the proposed theme. The categories analyzed were school cultures, subjects, practices and representations. Methodologically, the investigation was supported by documentary analysis and the documents used come from the following collections: Antônio Prado Historical Archive, João Spadari Adami Municipal Historical Archive, Padre Schio Museum, newspapers from Digital Hemeroteca, being the main ones A Federação, Stafetta, Il Colono and Panorama Pradense, local newspaper of Antônio Prado, in addition to consular reports and bibliographies that aproach the theme in the locality. The research made allowed the understanding of the emergence of teaching, used predominantly by families - through family education, private and subsidized classes emerge from the Italian Government, in addition to the presence of a College maintained by a religious institution. Regarding to public education, until the emancipation of the municipality in 1899, it had up to three classes, when expansion occurs, however until 1912 there are no permanent changes, but rotation of teachers, creation, establishment and displacement of classes frequently. The situation changes with the emergence of State Decree nº 1895/1912, which provided subsidies for public schooling in the countryside that affected subjects of foreign origin, so until 1920 quadruple classes in this place and public schools are characterized as the basis of schooling in the municipality. Regarding the subjects, it was possible to verify numerous initiatives carried out by the community, in addition, by measuring the literacy rate, it was possible to conclude that most of them had some level of literacy and acted in the development of schooling in the locality. The evidence also showed that there were many differences depending on the type of schooling and the location in which the school was located, reflecting on the practices, which in the case of public schools - more discussed due to the available documentation - were supported by discipline, order and adoption of values, marking the cultures of each class, discussed in dialogue with the context and the elements that compose them [ resumo fornecido pelo autor].
A presente dissertação narra o processo de escolarização na localidade de Antônio Prado - RS - entre os anos de 1886 a 1920. O estudo é vinculado à Linha de Pesquisa História e Filosofia da Educação do Programa de Pós-Graduação em Educação da Universidade de Caxias do Sul (UCS). O recorte temporal inicial, 1886, refere-se a criação da colônia e estabelecimento dos primeiros imigrantes, enquanto 1920 corresponde ao início das atividades escolares dos Irmãos Maristas, por se tratar de uma outra etapa no processo escolar do município. Os pressupostos teórico-metodológicos que orientam a pesquisa advêm da História Cultural e da História da Educação, a partir das contribuições de Certeau (1982, 1995), Febvre (1989), Le Goff (1990a, 1990b), Burke (1992, 2004, 2008), Chartier (1991a, 1991b, 2002a, 2002b, 2009, 2019) e Hall (2006) para a compreensão da investigação histórica-documental, dos sujeitos e das representações; enquanto o entendimento de culturas escolares, práticas e modos de escolarização baseia-se em Viñao Frago (1993, 1995, 2000 e 2005), Viñao Frago e Escolano (1998), Julia (2001), Faria Filho (2002, 2008), além de pesquisadores que dialogam com a temática proposta. As categorias analisadas foram culturas escolares, sujeitos, práticas e representações. Metodologicamente, a investigação apoiou-se na análise documental e os documentos utilizados provêm dos seguintes acervos: Arquivo Histórico de Antônio Prado, Arquivo Histórico Municipal João Spadari Adami, Museu Padre Schio, jornais da Hemeroteca Digital, sendo os principais A Federação, Stafetta, Il Colono e Panorama Pradense, jornal local de Antônio Prado e também relatórios consulares e bibliografias que abordam a temática na localidade. A pesquisa realizada permitiu o entendimento da emergência do ensino, realizado predominantemente pelas famílias - por meio da educação familiar -, concomitante emergem aulas particulares e subvencionadas pelo Governo Italiano, além da presença de um Colégio mantido por uma instituição religiosa. No que se refere ao ensino público, até a emancipação do município em 1899, ele contava com até três aulas quando ocorre expansão, todavia até 1912 não há mudanças permanentes, mas rodízio de professores, criação, estabelecimento e deslocamento das aulas frequentemente. A situação muda com a emergência do Decreto Estadual nº 1895/1912 que forneceu subsídios para a escolarização pública do interior que atingisse sujeitos de origem estrangeira, assim até 1920 quadriplicam as aulas no local e as escolas públicas se caracterizam como a base da escolarização do município. No que tange aos sujeitos, foi possível verificar inúmeras iniciativas realizadas pela comunidade, ademais, pela medição da taxa de alfabetização, conclui-se que em sua maioria possuíam algum nível de alfabetização e atuaram no desenvolvimento da escolarização da localidade. Os indícios também mostraram que existiam muitas diferenças a depender da modalidade de escolarização e do local no qual a escola estava situada, refletindo nas práticas, que no caso das escolas públicas - mais discutidas em virtude da documentação disponível - foi apoiada na disciplina, ordem e adoção de valores, marcando as culturas de cada aula, discutidas em diálogo com o contexto e os elementos que as compõem [ resumo fornecido pelo autor].
Keywords: Educação - História - Antônio Prado (RS); Education - History - Antônio Prado (Brazil)